CERTAIN TYPES OF GENERALIZED CLOSED SETS - Hameed, Najlae Falah (Al-Nahrain Journal of Science, 2018)
In this paper, we introduce and study new types of generalized closed subsets of topological space, and we will summarize the relationships between them and we will proved every pointed on it. Also we will introduce and study new types of continuous functions on it, also, we will summarize the relationships between them, and proved every pointed on it. Several properties of these concepts are proved.